2014
DOI: 10.1186/1472-6750-14-62
|View full text |Cite
|
Sign up to set email alerts
|

Generation and characterization of a new mammalian cell line continuously expressing virus-like particles of Japanese encephalitis virus for a subunit vaccine candidate

Abstract: BackgroundJapanese encephalitis virus (JEV) is the most important cause of epidemic encephalitis in most Asian regions. There is no specific treatment available for Japanese encephalitis, and vaccination is the only effective way to prevent JEV infection in humans and domestic animals. The purpose of this study is to establish a new mammalian cell line stably and efficiently expressing virus-like particle of JEV for potential use of JEV subunit vaccine.ResultsWe generated a new cell clone (BJ-ME cells) that st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 46 publications
(47 reference statements)
0
19
0
Order By: Relevance
“…Cell line development for stable production of VLPs has been used when the viral proteins are not cytotoxic. Two very recent examples are HEK-G cells developed for the production of rabies VLPs [107] and BJ-BM cells for the production of Japanese encephalitis virus VLPs [108] (Table 2). When the proteins are cytotoxic, transient approaches are used instead.…”
Section: Stable Cell Line Development For Constitutive Expression Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Cell line development for stable production of VLPs has been used when the viral proteins are not cytotoxic. Two very recent examples are HEK-G cells developed for the production of rabies VLPs [107] and BJ-BM cells for the production of Japanese encephalitis virus VLPs [108] (Table 2). When the proteins are cytotoxic, transient approaches are used instead.…”
Section: Stable Cell Line Development For Constitutive Expression Of mentioning
confidence: 99%
“…Stable expression of the structural gene pIX from human adenovirus increased the titers of poxvirus, the main viral product manufactured in AGE1 ® cells ( Table 3). The authors suggested that the improvement in viral titers is mediated via induction of heat shock pathway [108].…”
Section: Cell Line Engineeringmentioning
confidence: 99%
“…Similar immunogenicity/protection in mice and pigs was respectively observed when plasmids encoding JEV prME genes were stably expressed in rabbit kidney-derived RK13 and CHO cells [40,41]. Following the above discoveries, several other groups also expressed plasmid vectors encoding JEV prME genes to produce JEV VLPs in different mammalian cells, yielding similar immunogenicity/protection in mice [42,43]. On the other hand, many groups have also successfully used the insect cell expression system to generate JEV VLPs [44][45][46][47][48].…”
Section: Japanese Encephalitis Virusmentioning
confidence: 85%
“…Nevertheless, several systems are available for the expression of proteins in mammalian cells and have been successfully used to express candidate vaccine proteins for bovine viral diarrhea (BVD), 13 CSF, 14 and VLPs for Japanese encephalitis virus. 15…”
Section: Insect Cell Expressionmentioning
confidence: 99%